STABILITY ANALYSIS OF EQUALITY POINT MATHEMATICS MODEL OF INFLUENZA VIRUS IN THE HUMAN BODY WITH HERBAL TREATMENT THERAPY - Maharany Maharany; Mardiningsih Mardiningsih (MES: Journal of Mathematics Education and Science, 2022)
This study discusses a mathematical model for the transmission of influenza virus in the human body. The mathematical model used is the SITR model. As an effort to inhibit the influenza virus, the model is considered as herbal treatment therapy.The purpose of this study was to analyze the stability of the equilibrium point of the mathematical model of the influenza virus in the human body with herbal medicine therapy. The method used in analyzing the problem is literature study. The steps taken are determining the problem, literature study, analysis and problem solving and drawing conclusions. As a result of the research, the model obtained is. . From this model, there are two equilibrium points, namely the disease-free equilibrium point and the endemic equilibrium point. The analysis carried out resulted in the basic reproduction ratio number . After analyzing the two equilibrium points, it can be concluded that the disease-free equilibrium point will be locally asymptotically stable if . Meanwhile, the endemic equilibrium point will be locally asymptotically stable . Furthermore, to illustrate the model, a model simulation is carried out using the Maple.